Epistemology of Hadith in Syafi'iyyah And It’s Effect in Istinbāṭ Al-Ahkām - Imam Syafi'i; Subairi Subairi (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2022)
This study aims to examine the Hadith in the Syafi'iyah Ulama. Historically, the style of thought of the scholars has focused on two schools, namely: the mutakallim school pioneered by the Syafi'iyyah scholars and the Ahnāf school, known as the fuqahā', which the Hanafi scholars built. These two schools have different paradigms, including in the study of Hadith, especially when istinbāṭ al-Ahkām. There are three points obtained in this study; first, the Syafi'iyyah scholars divide the Hadith (from the aspect of quantity) into two, namely the mutawātir Hadith and the ahād Hadith. Second, the scholars agree that Mutawātir hadith can be used as a basis for a source of law. At the same time, the ahād Hadith and the mursal Hadith of the Syafi'iyyah scholars provide certain conditions in making the ahād Hadith and mursal Hadith sources of law. Third, from the aspect of qat'iy-ẓanniy and 'ām-takhs, in the view of the Syafi'iyyah scholars that the word 'āmm is Zanni, so the pronunciation of 'āmm, what is in the Qur'an can be interpreted with the Hadith ahād and Qiyas because they are both Zanni. Zanni argues that there is no obstacle to assessing the Zanni. Penelitian ini bertujuan untuk mengkaji tentang hadis dalam Ulama Syāfi’iyah. Dalam sejarahnya, corak pemikiran para ulama terpusat pada dua aliran, yaitu aliran mutakallimīn yang dipelopori oleh ulama Syāfi’iyyah dan aliran Ahnāf atau dikenal dengan fuqahā’ yang dibangun oleh ulama Hanafiyah. Dua aliran ini memiliki paradigma yang berbeda termasuk didalamnya dalam kajian Hadis, khususnya ketika istinbāṭ al-Ahkām. Ada tiga poin yang didapatkan dalam penelitian ini, pertama dalam aspek pembagian, ulama Syāfi’iyyah membagi hadis (dari aspek kuantitas) menjadi dua, yaitu Hadis mutawātir dan hadis ahād. Kedua dalam aspek kedudukan hadis dalam menggali hukum, dalam hal hadis Mutawātir para ulama sepakat bahwa hadis Mutawātir dapat dijadikan landasan sebagai sumber hukum. Sementara hadis ahād dan hadis mursal ulama Syāfi’iyyah memberikan syarat-syarat tertentu didalam menjadikan hadis ahād dan hadis mursal sebagai sumber hukum. Ketiga, dari aspek qat’iy-ẓanniy dan ‘ām-takhsīṣ, dalam pandangan ulama Syāfi’iyyah bahwa lafaz ‘āmm adalah ẓanni sehingga lafaz ‘āmm yang ada dalam al-Qur’an bisa di takhsīṣ dengan hadis ahād dan qiyas karena sama-sama bersifat ẓanni. Dalil ẓanni tidak ada halangan untuk men-takhshīṣ yang ẓanni.